1970
DOI: 10.1055/s-0028-1095049
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Pituitary "Fettstoffwechselhormon" - III. The Corticotropic Activity of Some Lipolytic Effective Hog Pituitary Gland Fractions in Vivo

Abstract: From the recently described lipolytically active pituitary g1and fraction P IV we isolated three other fractions with different lipid mobilizing effects. These fractions were checked far their corticotropic activity as ACfH belongs to the most active lipolytic hormones. The applied bioassay for ACfH was based on the determination of the corticosterone increase in the adrenal vein blood of hypophysectomized rats. All of the isolated fractions showed corticotropic activity.Horm Metab. Res. 2: 333-337 (1970) K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
1974
1974

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…After lyophilization the different fractions were desalted on Sephadex G 25, since former experiments had demonstrated that dialysis of the P -LF -fractions partially involved a relatively high loss of substance (Schleyer et al 1970).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After lyophilization the different fractions were desalted on Sephadex G 25, since former experiments had demonstrated that dialysis of the P -LF -fractions partially involved a relatively high loss of substance (Schleyer et al 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Even though P-LF I e and P-LF 11 d are not completely pure, we succeeded in isolating two fractions, which are free of corticotropic activity but showed about the same high lipolytic activity as ACTH. This does not apply for the nurnerous lipolytic active pituitary peptides reported the last 10 to 15 years (see Schleyer et al 1969aSchleyer et al , 1970. For most of these peptides it is discussed not at all or only insufficiently that already very low contaminations of ACTH may simulate high lipolytic activity of a peptide.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation